BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

How useful are volunteers for visual biodiversity surveys? An evaluation of skill level and group size during a conservation expedition - Andrea Albergoni; Ian Bride; Charles T. Scialfa; Merlijn Jocque; Steve Green (Biodiversity and Conservation, 2016)

Presence of amphibian chytrid fungus (Batrachochytrium dendrobatidis) in rainwater suggests aerial dispersal is possible - Jonathan E. Kolby; Sara D. Ramirez; Lee Berger; Dale W. Griffin; Merlijn Jocque; Lee F. Skerratt (Aerobiologia, 2015)

Dominant predators mediate the impact of habitat size on trophic structure in bromeliad invertebrate communities - Jana S. Petermann; Vinicius F. Farjalla; Merlijn Jocque; Pavel Kratina; A. Andrew M. MacDonald; Nicholas A. C. Marino; Paula M. de Omena; Gustavo C. O. Piccoli; Barbara A. Richardson; Michael J. Richardson; Gustavo Q. Romero; Martin Videla; et al. (Ecology, 2015)
Local habitat size has been shown to influence colonization and extinction processes of species in patchy environments. However, species differ in body size, mobility, and trophic level, and may not respond in the same way to habitat size. Thus far, we have a limited understanding of how habitat size influences the structure of multitrophic communities and to what extent the effects may be generalizable over a broad geographic range. Here, we used water‐filled bromeliads of different sizes as a natural model system to examine the effects of habitat size on the trophic structure of their inhabiting invertebrate communities. We collected composition and biomass data from 651 bromeliad communities from eight sites across Central and South America differing in environmental conditions, species pools, and the presence of large‐bodied odonate predators. We found that trophic structure in the communities changed dramatically with changes in habitat (bromeliad) size. Detritivore : resource ratios showed a consistent negative relationship with habitat size across sites. In contrast, changes in predator : detritivore (prey) ratios depended on the presence of odonates as dominant predators in the regional pool. At sites without odonates, predator : detritivore biomass ratios decreased with increasing habitat size. At sites with odonates, we found odonates to be more frequently present in large than in small bromeliads, and predator : detritivore biomass ratios increased with increasing habitat size to the point where some trophic pyramids became inverted. Our results show that the distribution of biomass amongst food‐web levels depends strongly on habitat size, largely irrespective of geographic differences in environmental conditions or detritivore species compositions. However, the presence of large‐bodied predators in the regional species pool may fundamentally alter this relationship between habitat size and trophic structure. We conclude that taking into account the response and multitrophic effects of dominant, mobile species may be critical when predicting changes in community structure along a habitat‐size gradient.

Small sample, substantial contribution: additions to the Honduran hawkmoth (Lepidoptera: Sphingidae) fauna based on collections from a mountainous protected area (Cusuco National Park) - Maarten P. M. Vanhove; Merlijn Jocque; Darren J. Mann; Shaun Waters; Thomas J. Creedy; Jose M. Nuñez-Miño; Ana C. Samayoa; Thierry Vaglia; Jeroen Casteels (Journal of Insect Conservation, 2012)

Climatic control of dispersal–ecological specialization trade‐offs: a metacommunity process at the heart of the latitudinal diversity gradient? - Merlijn Jocque; Richard Field; Luc Brendonck; Luc De Meester (Global Ecology and Biogeography, 2010)
We outline the potentially important role of dispersal in linking diversity patterns at different spatial and temporal scales, and the resulting potential to link hypotheses explaining macroscale patterns of diversity. We do this by proposing a possible mechanism linking climate to diversity patterns: we argue that climate, via effects of continuity of habitat availability in space and time, mediates a dispersal–ecological specialization trade‐off at the metacommunity level that leads to latitudinal trends in dispersal ability, ecological specialization, range sizes, speciation and species richness, ultimately driving the latitudinal diversity gradient. This trade‐off constitutes a possible mechanism for the strong macroscale correlation between climate and species richness that is consistent with recent ideas about niche conservatism and gradient lengths, as well as other leading hypotheses. We present an overview of predictions derived from our ideas. Of these, some have already been tested and supported and others are still open to debate or need testing. Together they provide a unique set of predictions that allows falsification.